ODARRL: Obstacle- and Disturbance-Aware End-to-End Residual Reinforcement Learning for Underwater Robot Trajectory Tracking with Obstacle Avoidance - Linghan Meng; Zebin Huang; Qingfeng Yao; Yunxiu Zhang; Qifeng Zhang (Journal of Marine Science and Engineering, 2026)
ROVs are essential for marine exploration and underwater operations, yet conventional teleoperation relies heavily on skilled human operators, and many autonomous methods stop at high-level planning rather than low-level actuation, limiting robustness in disturbed and cluttered environments. This paper proposes ODARRL, an obstacle- and disturbance-aware sensor-to-thruster (ST) end-to-end residual reinforcement learning framework for safe trajectory execution of underwater robots. Using a three-stage curriculum, ODARRL first acquires a basic policy from MPC demonstrations in a static obstacle-free environment, then improves disturbance-robust tracking under random currents, and finally extends to scenarios involving both currents and obstacles. A Dual-Horizon Attention Disturbance Encoder is further designed to capture current-related features from long- and short-term histories, which are fused with robot states and reference information as the input to the ST end-to-end policy. Experiments in Marine Gym with BlueROV2 Heavy demonstrate that ODARRL achieves more stable and robust trajectory tracking under random currents, reducing the mean total tracking error by 69.3%, 31.9%, 45.8%, 73.0% and 25.8% relative to the MPC-imitation policy, PPO, SAC, A2C and VNRS-SAC, respectively. With obstacles introduced, curriculum-initialized policies also exhibit higher path progress and more stable task completion during obstacle-avoidance training.

Improvement of Sparassis crispa polysaccharide quality by steam explosion technology: Physicochemical, structural and functional properties - Jingru Wu; Yueyue Qiang; Haoxuan Peng; Qiao Guan; Lei Pan; Zhiwei Huang; Zebin Guo; Jianbo Xiao; Baodong Zheng; Yafeng Zheng (Innovative Food Science & Emerging Technologies, 2026)

From morphological constraints to genomic SNPs: Developing population identification methods exemplified by large yellow croaker (Larimichthys crocea) - Zebin Zhou; Xubing Ba; Qianwen Min; Jiayu Zhou; Xin Yi; Ruojing Li; Bi Huang; Na Zhao; Bo Zhang; Songlin Chen (Aquaculture, 2026)

Penetration of benzotriazole ultraviolet stabilizers across the blood-cerebrospinal fluid barrier in patients with leptomeningeal metastasis - Yuxiang Weng; Chi Hu; Meng Wang; Zebin Fang; Feng Xiao; Luyuan Zhang; Chao Zhang; Ping Lan; Yu Zhu; Kaiyuan Huang (Journal of Hazardous Materials, 2026)

Gene cloning and expression analysis based on primary culture of fin cells from Centropyge vrolikii - Dingyuan Luo; Ning Xi; Shengkai Shi; Yizhen Lu; Zebin Chen; Hongwei Liu; Jincan Chen; Hai Huang; Zhaowei Zhong; Yonghua Jiang (Journal of Fish Biology, 2026)
Skin coloration is a distinctive phenotype and an economically important trait in ornamental fish. Understanding its regulatory mechanisms is crucial for both aquaculture and selective breeding. In this study, we cloned and analysed the full‐length complementary DNA (cDNA) sequences of four key pigmentation‐related genes— mitf , mc1r , tyr and sox10 —in the black‐tailed angelfish ( Centropyge vrolikii ). We established the fin‐derived tissue cell line of C. vrolikii (CVFTCL) and confirmed its transfection efficiency using EGFP, achieving 40%–50% expression 24 h post‐transfection, providing an in vitro platform for subsequent gene function verification. Using the primary fin cell culture system, we conducted overexpression and RNA interference (RNAi) experiments to investigate the regulatory relationships among these genes. Overexpression of mitf upregulated mc1r but downregulated sox10 and tyr ; overexpression of mc1r enhanced mitf expression while inhibiting sox10 and tyr ; overexpression of tyr only increased tyrp1 expression and overexpression of sox10 upregulated both mc1r and mitf , without affecting tyr . RNAi‐mediated knockdown confirmed the efficiency of gene silencing and supported the regulatory relationships inferred from overexpression experiments. Collectively, these findings indicate that mitf , mc1r , tyr and sox10 may interact to coregulate melanocyte development and melanin synthesis, thereby influencing skin coloration in C. vrolikii . This study provides a mechanistic framework for pigmentation regulation and a foundation for colour improvement and selective breeding in this species.

A case-control study linking concentrations of microplastics in human cerebrospinal fluid to intracranial aneurysm risk - Zebin Fang; Xiaoyi Wang; Fan Wu; Sihan Mao; Hao Jiang; Chi Hu; Luyuan Zhang; Weijian Fan; Chao Zhang; Ping Lan; Kaiyuan Huang; Yuxiang Weng; et al. (Environmental Pollution, 2026)

Ellagic acid-mediated interfacial bonding Co/Fe heterobimetallic complex for dually enhanced hole transfer and water oxidation of BiVO4 photoanode - Hongcheng Huang; Mingjie Li; Boge Zhang; Ronghua Jiang; Jun Huang; Zimu Zhang; Zifei Xie; Yanjie Zhou; Zebin Yu (Chemical Engineering Journal, 2025)

Machine learning-guided multi-objective optimization for selective lithium extraction and valuable metal reuse from spent lithium-ion batteries - Jiayi Qu; Boge Zhang; Ronghua Jiang; Jun Huang; Mingjie Li; Sicheng Zheng; Wenjing Yu; Pengxin Sun; Yihua Xu; Yanping Hou; Hongfei Lin; Zebin Yu (Chemical Engineering Journal, 2025)

Cobalt doping modulation of Cs4MnBi2Cl12 double perovskite induces spin polarization for boosting photocatalytic reduction of CO2 - Yan Huang; Yujia Liu; Yi Liu; Xinqiu Tan; Yikai Wang; Qian Xiao; Xiaoyu Tong; Jinghui Pan; Zebin Yu; Zuofang Yao; Yanping Hou (Chemical Engineering Journal, 2025)

Seasonal dynamics of ammonia-oxidizing archaea and bacteria in subalpine forests of western Sichuan - Li Zhang; Su Chen; Zebin Jiao; Sining Liu; Wenlan Huang; Lulu Huang; Liyun Yu; Lixia Wang; Bo Tan; Hongwei Xu; Lin Xu; Chengming You; et al. (Plant and Soil, 2025)

Enhanced biodegradation of sulfamethazine in swine manure composting: Pathway elucidation, mechanism insights, and optimization of a novel Bacillus sp. strain - Xiaojun Lin; Jingtong Li; Chunyan Chen; Zifeng Luo; Hongxing Tu; Yuwan Pang; Xiujuan Wang; Qianyi Cai; Zebin Wei; Jianfeng Huang; Jingwen Zeng; Jinrong Qiu (International Biodeterioration & Biodegradation, 2025)

Redox-active ligands for oxygen evolution reactions activity: Modulation of metal valence states in synthesis and accelerated reconstruction by rapid hydrolysis in alkaline electrolytes - Pengxin Sun; Jing Liu; Li Wang; Cheng Wu; Ronghua Jiang; Jun Huang; Yanping Hou; Mingjie Li; Boge Zhang; Zebin Yu (Journal of Environmental Chemical Engineering, 2025)

Strong, flame-retardant, and smoke-suppressive green composites enabled by a simple and effective synergistic mineralization strategy - Shenghui Lai; Jing Liu; Tao Yang; Jinzhuo Huang; Yinghe Wang; Zebin Deng; Da Liu; Guangming Yuan; Shuaiming He (Chemical Engineering Journal, 2025)

Response surface methodology and Box-Behnken design optimization of Sulfaquinoxaline removal efficiency and degradation mechanisms by Bacillus sp. strain DLY-11 - Chunyan Chen; Zifeng Luo; Hongxing Tu; Xiaojun Lin; Yuwan Pang; Jianfeng Huang; Jun Zhang; Xiujuan Wang; Qianyi Cai; Zebin Wei; Jingwen Zeng; Jinrong Qiu (Journal of Hazardous Materials, 2025)

Ameliorative effects of Trichosanthes kirilowii Maxim. seed oil on hyperlipidemia rats associated with the regulation of gut microbiology and metabolomics - Weili Chen; Zhangbao Zhou; Ruida Qi; Jun Zhou; Huiying Liang; Pinxi Huang; Zebin Zou; Ling Dong; Hua Li; Bing Du; Pan Li (Food Research International, 2024)

Marine glycoproteins: a mine of their structures, functions and potential applications - Xiaodan Lu; Luyao Huang; Jiaqi Chen; Yujia Ou; Jingru Wu; David Mahoudjro Bodjrenou; Jiamiao Hu; Yi Zhang; Mohamed A. Farag; Zebin Guo; Jianbo Xiao; Baodong Zheng (Critical Reviews in Food Science and Nutrition, 2024)

Vacancy engineering-induced spin polarization in heterogeneous phosphides by simple iron salt infiltration for efficient overall water splitting - Xuanning Qin; Zebin Yu; Zimu Zhang; Zuoyu Qin; Han Pang; Boge Zhang; Yanping Hou; Jun Huang; Ronghua Jiang; Jiayi Qu (Chemical Engineering Journal, 2024)

Genome-wide identification of toll-like receptors in Octopus sinensis and expression analysis in response to different PAMPs stimulation - Zebin Chen; Yuquan Zhou; Xinxin Chen; Yinzhen Sheng; Jiaqian Liao; Yicong Huang; Xiao Zhong; Jianming Zhang; Youfang Zhu; Ziping Zhang; Yilei Wang (Fish & Shellfish Immunology, 2024)

Delineation of urban growth boundary based on FLUS model under the perspective of land use evaluation in hilly mountainous areas - Yunping Zhang; Jianping Lin; Yimin Huang; Zebin Chen; Chenhui Zhu; Hao Yuan (Journal of Mountain Science, 2024)

Differences in particulate matter retention and leaf microstructures of 10 plants in different urban environments in Lanzhou City - Rong Huang; Qing Tian; Yue Zhang; Zhini Chen; Yonghua Wu; Zizhen Li; Zebin Wen (Environmental Science and Pollution Research, 2023)

Geothermal springs with high δ13CCO2-DIC along the Xianshuihe fault, Western Sichuan, China: A geochemical signature of enhanced deep tectonic activity - Jinlong Liang; Yi Yu; Zeming Shi; Zhipeng Li; Yi Huang; Hao Song; Jinyong Xu; Xinyu Wang; Xiaocheng Zhou; Luyu Huang; Zebin Luo; Jue Tong; et al. (Journal of Hydrology, 2023)

Effects of climate change on the geographical distribution and potential distribution areas of 35 Millettia Species in China - Kai Zhao; Xuetong Li; Jingru Yang; Zebin Huang; Chunlian Li; Lewen Yao; Zekai Tan; Xianyi Wu; Shiyuan Huang; Yanghe Yuan; Zhengyi Hong; Qiuyang Cai; et al. (Environmental Science and Pollution Research, 2022)

Ball-milled biochar for alternative carbon electrode - Honghong Lyu; Zebin Yu; Bin Gao; Feng He; Jun Huang; Jingchun Tang; Boxiong Shen (Environmental Science and Pollution Research, 2019)

Alginate-based composites for environmental applications: a critical review - Bing Wang; Yongshan Wan; Yuling Zheng; Xinqing Lee; Taoze Liu; Zebin Yu; Jun Huang; Yong Sik Ok; Jianjun Chen; Bin Gao (Critical Reviews in Environmental Science and Technology, 2019)

Nutritional composition, physiological functions and processing of lotus (Nelumbo nucifera Gaertn.) seeds: a review - Yi Zhang; Xu Lu; Shaoxiao Zeng; Xuhui Huang; Zebin Guo; Yafeng Zheng; Yuting Tian; Baodong Zheng (Phytochemistry Reviews, 2015)

The exon 29 c.3535A>T in the alpha-2-macroglobulin gene causing aberrant splice variants is associated with mastitis in dairy cattle - Xiuge Wang; Jinming Huang; Lihong Zhao; Changfa Wang; Zhihua Ju; Qiuling Li; Chao Qi; Yan Zhang; Zebin Zhang; Wei Zhang; Minghai Hou; Jinduo Yuan; et al. (Immunogenetics, 2012)